Applied occlusion - Wassell, R. W. (London ; Chicago : Quintessence, 2008)
No further information has been provided for this title.
DVD contents: Understanding jaw movement animations. Intercuspal position (ICP) -- Lateral excursion into ICP showing disclusion -- Canine guidance and group function -- Tracks of posterior movement -- Crowning and anterior guidance -- Protrusive interference on crown -- Retruded contact position and ICP -- Last tooth in the arch syndrome -- Cross arch pivot -- Clinical and laboratory sequences. TMD examination -- Occlusal examination -- accurate alginate impressions -- Centric relation registration -- Facebow record -- Semi-adjustable and average value articulator -- Mounting casts -- Occlusal analysis -- Trial occlusal adjustment -- Clinical occlusal adjustment and follow-up.
Includes bibliographical references and index.
Keywords: Malocclusion -- diagnosis; Dental Occlusion; Malocclusion -- therapy; Occlusion (Dentistry)